Alternative view on niche development: situated learning on policy communities, power and agency. Issue 1 (2nd January 2016) - Ratinen, Mari; Lund, Peter D.
ABSTRACT: In this article, we analyse how situated learning influences niche development. Situated learning is tied to social action and context, perceiving knowledge and learning as socially constructed. In addition, a dialectic view of structure and agency is adopted. Policymaking is used as an example of a community. A qualitative case study of Finnish energy policy is presented. The regime in Finland is the electricity industry that supports bioenergy, while wind energy development is supported by active individuals and a few niche actors. The full-members of the policymaking community consist of the government and the regime actors. The niche actors did learn how the community functions and developed alternative strategies accordingly, but without success. A reason could be that the niche actors excluded the regime from their strategies. We conclude that situated learning is likely to enhance niche development, but compromises in niche development may be needed.